LATIN 2008 - Theoretical Informatics: 8th Latin American Symposium, Búzios, Brazil, April 7-11, 2008, Proceedings - Laber, Eduardo Sany; Bornstein, Claudson; Nogueira, Loana Tito; Faria, Luerbio (Lecture Notes in Computer Science, 2008)
This proceedings volume examines a range of topics in theoretical computer science, including automata theory, data compression, logic, machine learning, mathematical programming, parallel and distributed computing, quantum computing and random structures.